2015
DOI: 10.4155/fso.14.2
|View full text |Cite
|
Sign up to set email alerts
|

Interfacing Antibody-Based Microarrays and Digital Holography Enables Label-Free Detection for Loss of Cell Volume

Abstract: Background:We introduce the combination of digital holographic microscopy (DHM) and antibody microarrays as a powerful tool to measure morphological changes in specifically antibody-captured cells. The aim of the study was to develop DHM for analysis of cell death of etoposide-treated suspension cells.Results/methodology:We demonstrate that the cell number, mean area, thickness and volume were noninvasively measured by using DHM. The cell number was stable over time, but the two cell lines showed changes of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…For the U2932 cell line, the average cell area did not change, whereas the average cell volume significantly decreased after etoposide treatment (Figure 2). Interestingly, the results may indicate cell line sensitivity, which also has been shown in the earlier studies [25,27]. In conclusion, cell death experiments performed with DH microscopy reveal that small differences between two cell lines can be clarified.…”
Section: Cell Death Of Adherent Cellssupporting
confidence: 60%
See 2 more Smart Citations
“…For the U2932 cell line, the average cell area did not change, whereas the average cell volume significantly decreased after etoposide treatment (Figure 2). Interestingly, the results may indicate cell line sensitivity, which also has been shown in the earlier studies [25,27]. In conclusion, cell death experiments performed with DH microscopy reveal that small differences between two cell lines can be clarified.…”
Section: Cell Death Of Adherent Cellssupporting
confidence: 60%
“…The cell number was stable over time, but the two cell lines used showed changes of cell area and cell irregularity after treatment. The cell volume in etoposide-treated cells was decreased, whereas untreated cells showed stable volume [27]. In conclusion, cell death of suspension cells investigated with the help of antibody-based microarrays and DH demonstrated that morphological parameters can be investigated of different cell lines and treatments.…”
Section: Cell Death Of Suspension Cells On Antibody-based Microarraymentioning
confidence: 98%
See 1 more Smart Citation
“…DHC applications have previously been used to discriminate between the maturity levels of red blood cells, perform cell death studies and analyze drug responses [23,[37][38][39]. Cell optical area, thickness and volume are useful parameters, particularly for discrimination between different cell types [39][40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Although for fixed applications, suspension cells may be attached to coverslips by cytocentrifugation such as cytospin technology 55 , a live-cell imaging setup is normally not compatible with suspension cells. DHM has previously been performed on live suspension cells immobilized by antibody capture 56 . Here, we tested the option to use thin 3D gels to immobilize suspension cells for multifield monitoring.…”
Section: Dhm Analysis Of Suspension Cells Embedded In Matrigel Can Qumentioning
confidence: 99%